Modeling improvements in ileal digestible amino acids by a novel consensus bacterial 6-phytase variant in broilers - Dersjant-Li Y; Bello A; Stormink T; Abdollahi MR; Ravindran V; Babatunde OO; Adeola O; Toghyani M; Liu SY; Selle PH; Marchal L (Elsevier, 2022)
Data from 13 datasets from 4 trials on the effect of a novel consensus bacterial 6-phytase variant (PhyG) on the apparent ileal digestibility (AID) of amino acids (AA) in broilers were used to model AID AA responses. The datasets were obtained from 3 trial locations (New Zealand, Australia and United States) and collectively incorporated variations in diet composition (feedstuff composition, phytate-P (PP) level, limestone solubility), feed form (mash or pellet), bird genetics (strain), and age at sampling (11–35 d of age). In total, 384 observations were analyzed. First, the relationships between AID of AA (as coefficients) and increasing phytase dose level from 0 to 4,000 FTU/kg were evaluated across all datasets using exponential curve fitting. Second, the percentage unit change in AID of AA at each phytase dose level from baseline (basal diet [BD] without phytase) was calculated separately for each dataset and the data then modeled together using exponential curve fitting. The model-predicted mean coefficient of AID of total AA in basal diets was 0.76 (range 0.56 [Cys] to 0.83 [Glu]), which was increased by PhyG to 0.80 and 0.81 at 2,000 and 4,000 FTU/kg, respectively. Exponential increases in the percentage unit improvement in AID of 18 individual and of total AA with increasing phytase dose level were evident (P < 0.05). Improvements (vs. BD) at 2,000 FTU/kg and 4,000 FTU/kg, respectively, were greatest for Cys (+9.2 and +11.0% units), Met (after deduction of synthetic Met, +8.4 and +9.0% units), and Thr (after deduction of synthetic Thr, +6.2 and +7.3% units). The data demonstrated consistent improvements in the AID of AA by the phytase. The modeling results generated from data gathered from birds sampled at different ages and from different dietary settings with correction of synthetic AA for Lys, Met, Thr, and Trp, enabled a more accurate prediction of the digestible AA contribution from the diet by this novel phytase. This will allow diet-specific AA matrix recommendations to be made in commercial feed formulations.
Keywords: amino acids; broiler; digestibility; nutrient matrix; phytate; 6-Phytase; Amino Acids; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Chickens; Dietary Supplements; Digestion